2015
DOI: 10.1080/02626667.2014.967695
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts on streamflow and sediment yield in the North of Iran

Abstract: Climate change will accelerate the hydrological cycle, altering rainfall, and the magnitude and timing of runoff. The purpose of this paper is to assess the impacts of climate change on streamflow and sediment yield from the Gorganroud river basin in the North of Iran. To study the effects of climatic variations, the SWAT model was implemented to simulate the hydrological regime and the SUFI-2 algorithm was used for parameter optimization. The climate change scenarios were constructed using the outcomes of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 29 publications
6
36
1
Order By: Relevance
“…It has been revealed in a study conducted by Adem et al [51] in the Upper Gilgel Abay of the Blue Nile Basin in Ethiopia that sediment yield was related to a change in climate variables and thus to streamflow. The variation in the values of sediment yield due to streamflow change that resulted from climate change has also been reported by many scholars [12,17,26,54,55]. In a similar study, average annual sediment loads generally decreased in response to climate change by 23.5% and 3.3% under RCP4.5 and RCP8.5, respectively in the mid-century (2046-2065) [15].…”
Section: Effect Of Climate Change On Lake Sedimentationsupporting
confidence: 74%
See 1 more Smart Citation
“…It has been revealed in a study conducted by Adem et al [51] in the Upper Gilgel Abay of the Blue Nile Basin in Ethiopia that sediment yield was related to a change in climate variables and thus to streamflow. The variation in the values of sediment yield due to streamflow change that resulted from climate change has also been reported by many scholars [12,17,26,54,55]. In a similar study, average annual sediment loads generally decreased in response to climate change by 23.5% and 3.3% under RCP4.5 and RCP8.5, respectively in the mid-century (2046-2065) [15].…”
Section: Effect Of Climate Change On Lake Sedimentationsupporting
confidence: 74%
“…Ayele et al [25] also used the SWAT model for sediment yield prediction in the Upper Blue Nile Basin. Cousino et al [15] and Azari et al [26] have also applied the SWAT model to evaluate the impact of climate change on sediment yield.…”
Section: Introductionmentioning
confidence: 99%
“…However, these results are not in agreement with the finding of Angelina et al [20] who showed an increase of mean annual flow of the Niger river basin at Koulikoro by 6.9% (2026-2050), 0.9% (2051-2075), and 5.6% (2076-2100) by using a SWAT model under the SRES A1B emissions scenario. Additionally, Azari et al [12] showed an increase in stream-flow under RCP4.5 and RCP8.5 in the Gorganroud River basin in the North of Iran. The differences in hydrological models used as well as the area of study (difference in climate, soil, relief, land use, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Increased evaporation, combined with changes in precipitation, has the potential to affect runoff, the frequency and intensity of floods and droughts, soil moisture, and available water for irrigation and hydroelectric generation [4]. Azari et al [12] highlighted that a long trend increase in temperature will considerably impact the hydrological cycle, thus changing rainfall pattern and the magnitude and timing of runoff. In Africa, climate change and its impact on water resources availability in space and time have put complex challenges to the African countries in their objective to better manage water resources and improve food security [13].…”
Section: Introductionmentioning
confidence: 99%
“…The impacts on hydrological processes are mainly caused by temperature increases and precipitation variations, generating increased stream flows and extreme weather events (ArreguĂ­n-CortĂ©s & LĂłpez-PĂ©rez, 2013;Azari, Moradi, Saghafian, & Faramarzi, 2016;Wu, Qian, Li, & Song, 2014b). Flash floods are regarded as a result of climatic changes and poor drainage infrastructure and have been frequently reported in China in recent years, causing casualties and enormous economic losses.…”
Section: Water Resources Research To Support a Sustainable Chinamentioning
confidence: 99%